Microcephaly primary hereditary (MCPH): Report of novel ASPM variants and prenatal diagnosis in a Vietnamese family - Thinh Huy Tran; Quang Minh Diep; My Ha Cao; Long Hoang Luong; Van Anh Pham; Oanh Thi Lan Dinh; The-Hung Bui; Thanh Van Ta; Van Khanh Tran (Elsevier, 2021)
Objective: MCPH (microcephaly primary hereditary) is a group of autosomal recessive developmental disorders with microcephaly present at birth and intellectual disability. Since a second trimester ultrasound is not able to detect subtypes with minimal prenatal presentations, only prenatal diagnosis by genetic testing can confirm these cases and allow for effective genetic counseling, especially a family with a previously affected child. Case Report: A 37-year-old women was pregnant for the third time and had two prior children with profound microcephaly and mental retardation. Targeted panel sequencing identified novel compound heterozygous ASPM pathogenic variants: c.1615_1616del (p. Glu539ArgfsTer15); c.∗293T > A (p. Leu98Ter), which confirmed the diagnosis of MCPH5 (#OMIM 608716). Genetic testing was conducted for family members and applied on prenatal diagnosis. Conclusion: This is the first cases of MCPH5 to be reported in Vietnam and the genetic result aided in prenatal diagnosis of a high-risk pregnancy. The study highlights the importance of genetic testing in defining definitive diagnosis which allowed for timely prenatal diagnosis and genetic counseling for the family.